Tiempo, comprensión y ciencia literaria: el papel del Estado en la aprehensión cultural - Alfaro Vargas, Roy (2008)
This article develops the division social time-physical time inside the environment of political centralization carried out by the government as a mean of political domination in the processes of cultural apprehension. It also sets up the negativity as a mean to surpass (aufheben) the division of such temporalities.